Novel Method for Sidelobe Level Suppression in Multielement Angled Dipole Array Antennas - Heesu Wang; Gangil Byun; Yong Bae Park; Ikmo Park (IEEE Access, 2022)
In this paper, we propose a one-dimensional (1D) array antenna with improved sidelobe level (SLL) and cross-polarization (x-pol) characteristics. The array elements constituting the 1D array antenna comprise different numbers of dipole elements, and each array element has a different gain and E-field phase. The positions of the array elements in the z-axis direction are adjusted to equalize their E-field phases in the far field, and the array elements are arranged symmetrically with respect to the z-axis to obtain a low x-pol. The same amount of power is supplied to all the array elements of the 1D array antenna of the proposed structure. Therefore, a complexly structured feeding network is not required to achieve a low SLL and low x-pol. The gain of the proposed array antenna with a corporate feeding network is 15.2 dBi, and its SLL and x-pol level are–21.3 dB and 20.3 dB, respectively. The–10 dB impedance bandwidth of the proposed array antenna is 35.6% (8.3–11.9 GHz).